Endoscopy in the Management of Complications of Acute Pancreatitis - Patel, Nicole; Shah, Ishani; Wadhwa, Vaibhav; Sawhney, Mandeep S. (Digestive Disease Interventions, 2022)
Acute pancreatitis (AP) is an acute necroinflammatory condition of the pancreas and one of the most common gastrointestinal conditions requiring hospitalization. Over the past decade, treatment of such AP-related complications has been majorly focused on incorporating a multidisciplinary approach involving distinct endoscopic, radiologic, and surgical interventions. Our review focuses on the role of endoscopic interventions in the management of local complications associated with AP, such as pancreatic fluid collections, walled-off necrosis, and pancreatic duct disruption.
Keywords: acute pancreatitis; endoscopy; pseudocyst